Therapeutic potential of coumestan pks13 inhibitors for tuberculosis - Lun, S.; Xiao, S.; Zhang, W.; Wang, S.; Gunosewoyo, Hendra; Yu, L.F.; Bishai, W.R. (AMER SOC MICROBIOLOGY, 2021)
Polyketide synthase 13 (Pks13) is an important enzyme found in Mycobacterium tuberculosis that condenses two fatty acyl chains to produce a-alkyl b-ketoesters, which in turn serve as the precursors for the synthesis of mycolic acids that are essential building blocks for maintaining the cell wall integrity of M. tuberculosis. Coumestan derivatives have recently been identified in our group as a new chemotype that exerts its antitubercular effects via targeting of Pks13. These compounds were active on both drug-susceptible and drug-resistant strains of M. tuberculosis and showed low cytotoxicity to healthy cells and a promising selectivity profile. No cross-resistance was found between the coumestan derivatives and first-line tuberculosis (TB) drugs. Here, we report that treatment of M. tuberculosis bacilli with 15 times the MIC of compound 1, an optimized lead coumestan compound, resulted in a CFU reduction from 6.0 log10 units to below the limit of detection (1.0 log10 units) per ml of culture, demonstrating a bactericidal mechanism of action. Single-dose (10mg/kg of body weight) pharmacokinetic studies revealed favorable parameters with a relative bioavailability of 19.4%. In a mouse infection and chemotherapy model, treatment with compound 1 showed dose-dependent monotherapeutic activity, whereas treatment with 1 in combination with rifampin showed clear synergistic effects. Together, these data suggest that coumestan derivatives are promising agents for further TB drug development.